ACCOUNT OF PECULIARITIES PERTAINING TO FORMATION OF SURFACE RUN-OFF QUALITY FROM TERRITORIES OF MACHINE-BUILDING ENTERPRISES WHILE CONSTRUCTING AND OPERATING WASTE WATER TREATMENT SYSTEMS - A. N. Kolobaev; O. K. Novikova (Наука и техника)
The paper reveals an influence of storm water quality from territories of machine-building enterprises on parameters of waste water treatment systems. «The criterion of relative storm water stabilization» has been theoretically justified and experimentally proved in the paper. This criterion makes it possible to carry off main quantity of contamination and storm water of an enterprise while passing waste water treatment systems.